Phenol degradation by advanced Fenton process in combination with ultrasonic irradiation - F.Z. Yehia; Gh. Eshaq; A.M. Rabie; A.H. Mady; A.E. ElMetwally (Egyptian Journal of Petroleum)
In this study, a successful degradation of phenol was achieved by means of coupling nano-sized zero-valent iron (NZVI), H2O2 and 20 kHz ultrasound irradiation. The effect of H2O2 concentration, initial pH, ultrasonic irradiation time and NZVI addition on the degradation efficiency was investigated and the kinetics of the process was discussed. The results showed that the degradation rate increased by increasing the H2O2 concentration and the irradiation time but decreased with the increase of the initial pH value. These results clearly indicate that the degradation of phenol is intensified in the presence of NZVI and H2O2, which can be attributed to enhanced production of ·−OH radicals in the system. The degradation rate in the presence of NZVI was faster than in its absence. Thus, an appropriate selection of operating conditions will lead to an economical and highly efficient technology with eventual large-scale commercial applications for the degradation of organic pollutants in aqueous effluents.